Building leaders for the UN Ocean Science Decade: a guide to supporting early career women researchers within academic marine research institutions. (16th December 2022) - Shellock, R J; Cvitanovic, C; McKinnon, M C; Mackay, M; van Putten, I E; Blythe, J; Kelly, R; Tuohy, P; Maltby, K M; Mynott, S; Simmonds, N; Bailey, M; et al.
Abstract: Diverse and inclusive marine research is paramount to addressing ocean sustainability challenges in the 21st century, as envisioned by the UN Decade of Ocean Science for Sustainable Development. Despite increasing efforts to diversify ocean science, women continue to face barriers at various stages of their career, which inhibits their progression to leadership within academic institutions. In this perspective, we draw on the collective experiences of thirty-four global women leaders, bolstered by a narrative review, to identify practical strategies and actions that will help empower early career women researchers to become the leaders of tomorrow. We propose five strategies: (i) create a more inclusive culture, (ii) ensure early and equitable career development opportunities for women ECRs, (iii) ensure equitable access to funding for women ECRs, (iv) offer mentoring opportunities and, (v) create flexible, family-friendly environments. Transformational, meaningful, and lasting change will only be achieved through commitment and collaborative action across various scales and by multiple stakeholders.